PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKANHASIL BELAJAR IPS SISWA KELAS IV SDN 161 PEKABARU - Diana Putri Sari; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This reseach was motivated by the low learning outcomes of class IV at Pekanbaru Public Elementary School 161 on social students. This study aims to improve social studies learning outcomes of class IV at pekanbaru Public Elementary School 25 by applying the cooperative learning model type numbered heads together. The research subjectse were class IV student at pekanbaru public Element school 161 which numbered 25 students. The results of the studies learnig outcomes of class IV students at pekanbaru public Elementary school 161 in thr academic year 2018/2019. This was evident from the student learning outcomes in the basic score is 72,20% to 24,22%, increasing by 23.45%. the avage from the base score to the second cycle to 2,72% increased by 90,4%. From the results of the study, it can be concluded that the application of the numbered heads together cooperative learning model can improve the social studies learning outcomes of class IV student at pekanbaru public elementary School 161.Keywords: cooperative learning model type numbered head together, social studies learning outcomes